Aplicación pedagógica del equipo (analizador de tres gases F-950) en procesos de transformación agroindustrial - Hernández Bonilla, Cinthya Alejandra (2022)
Pedagogy is a science that has a great impact on development individual as a social subject and the Universidad Técnica de Cotopaxi a way to improve the methodology at teaching-learning process intends new pedagogical equipment implementation that will help to a better understanding on carried out processes in the bromatology laboratory at fruits and vegetables area of the Agroindustrial Engineering career. For pedagogical application of the equipment (three-gas analyzer F-950) in agroindustrial transformation processes, an equipment operation manual was previously developed, as well as a maintenance manual, according to manufacturer's technical recommendations and laboratory practices that will serve as students´ guide at their learning process. These instructions allow correct and pedagogical application of the equipment (three-gas analyzer F-950). At laboratory practices following fruits were used: tomato (Solanum lycopersicum), blackberry (Rubus ulmifolius), strawberry (Fragaria) and vegetables: lettuce (Lactuca sativa). The obtained results were: strawberries at room temperature 161.8 ppm (C2H4), 21.2% (O2) and 0.71% (CO2), strawberries at controlled temperature 1.3 ppm (C2H4), 21.2% (O2) and 0.71% (CO2). On ripening process of blackberry that emanates ethylene to tomato 6.3 ppm (C2H4), 15.4% (O2) and 9.88% (CO2). Packaged lettuce 8.1 ppm (C2H4), 0.5% (O2) and 23.53% (CO2) and unpackaged lettuce 4.4 ppm (C2H4), 21.2% (O2) and 0.50% (CO2).